Hardiness dengan Subjective Well Being pada Remaja Panti Asuhan - Zulfiyah Khasanah; Siti Nur Asiyah (Universitas Ahmad Dahlan, 2021)
Hardiness With Subjective Well Being on Adolescent OrphanageSome Chirdlen, including adolescent, live witih their parents or family. However, not all adolescent can have a complate family, one of which is an orphanage adolescent. The orphanage adolescent need to have subjective well being more able to feel life satifaction. One of the positive personality that can influence subjective well being is hardiness. Individual who haveÂ hardiness personality will be able to survive when facing stressful events, so that they will feel more positive emotions. The study intends to develop corelation between hardiness with subjective well being of adolescent orphanage. Subject of the research were 40 adolescent orphanage from 3 orphanage, collected by purposive sampling. The measuring tool used consist of two scale, namely the scale of hardiness and subjective well being scale. Hypotesis testing in this research uses product moment with the help of SPSS. Product moment result indicated that hardiness has significant correlation with subjective well being with a significance value 0.00 <0.05 and coreelation value 0.702.Â Hardiness also contributes of subjective well being of 49.3%. Hardiness and subjective well being has positive corelation. It means that the higher of orphanage adolescentâ€™s hardiness, the higher their subjective well being too.